Measuring the Nature of the Relationship between the Dimensions of fear marketing: A survey study of the opinions of a sample of customers of Tariq Al-Agha General Trading Company in Mosul (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research aims to measure the nature of the relationship between the dimensions of fear marketing, represented by (fear of missing opportunities, fear of product scarcity, fear of losing the product, fear of followers and influencers) at Tariq Agha General Trading Company in Mosul, which was the field of research, as data was collected from the research sample, which amounted to (200) individuals, who are the company's permanent customers, using the questionnaire, which is the main tool for collecting data, and analyzing it based on the statistical program (SPSS v.22) to reach a solution to the research problem, which is "What is the nature of the relationship between the dimensions of fear marketing in the company under study from the point of view of customers?" Which aroused the interest of the researchers to adopt the dimensions of fear marketing, as it is a pattern that contributes to achieving the goals of the company under study, and one of the most prominent results that were reached is the existence of a significant and positive correlation between the dimensions of fear marketing, and the research presented a set of proposals, including: that the organization under study take into account the (price) it obtains compared to the services and effort made by the staff in the company.